2010
DOI: 10.1136/jnis.2009.001818
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with angioplasty of symptomatic M2 MCA atheromatous lesions

Abstract: Angioplasty of M2 MCA lesions is technically feasible in our cohort of neurologically unstable patients, but the durability of this treatment will require more extensive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…This is comparable with other small artery ICAD studies with reported success rates of 98.1 to 100%, with the only technical difficulty due to failure of wingspan stent deployment in a tortuous M2 lesion 14-17 . Furthermore, there were no peri-procedural complications in our patients, which is also similar to previously published case series (Table 2).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is comparable with other small artery ICAD studies with reported success rates of 98.1 to 100%, with the only technical difficulty due to failure of wingspan stent deployment in a tortuous M2 lesion 14-17 . Furthermore, there were no peri-procedural complications in our patients, which is also similar to previously published case series (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…The patient was re-treated with PTAS with no further instent restenosis (ISR) during follow up. In other small ICAD publications, the overall restenosis rate for primary angioplasty was 40.0% (all symptomatic) and 27.7% for PTAS (only 5.6% symptomatic) 14-17 . Studies examining large artery ICAD have stated variable ISR rate for the Wingspan system.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations